Hepatitis B virus X protein induces RNA polymerase III-dependent gene transcription and increases cellular TATA-binding protein by activating the Ras signaling pathway. - Wang, H D (1997)
Our previous studies have shown that the hepatitis B virus protein, X, activates all three classes of RNA polymerase III (pol III)-dependent promoters by increasing the cellular level of TATA-binding protein (TBP) (H.-D. Wang et al., Mol. Cell. Biol. 15:6720-6728, 1995), a limiting transcription component (A. Trivedi et al., Mol. Cell. Biol. 16:6909-6916, 1996). We have investigated whether these X-mediated events are dependent on the activation of the Ras/Raf-1 signaling pathway. Transient expression of a dominant-negative mutant Ras gene (Ras-ala15) in a Drosophila S-2 stable cell line expressing X (X-S2), or incubation of the cells with a Ras farnesylation inhibitor, specifically blocked both the X-dependent activation of a cotransfected tRNA gene and the increase in cellular TBP levels. Transient expression of a constitutively activated form of Ras (Ras-val12) in control S2 cells produced both an increase in tRNA gene transcription and an increase in cellular TBP levels. These events are not cell type specific since X-mediated gene induction was also shown to be dependent on Ras activation in a stable rat 1A cell line expressing X. Furthermore, increases in RNA pol III-dependent gene activity and TBP levels could be restored in X-S2 cells expressing Ras-ala15 by coexpressing a constitutively activated form of Raf-1. These events are serum dependent, and when the cells are serum deprived, the X-mediated effects are augmented. Together, these results demonstrate that the X-mediated induction of RNA pol III-dependent genes and increase in TBP are both dependent on the activation of the Ras/Raf-1 signaling cascade. In addition, these studies define two new and important consequences mediated by the activation of the Ras signal transduction pathway: an increase in the central transcription factor, TBP, and the induction of RNA pol III-dependent gene activity.